Post-Conflict Elections or Post-Elections Conflict: Sierra Leone 2002 and Patterns of Voting in Sub-Saharan Africa - David Harris (Cadernos de Estudos Africanos)
Sierra Leone is just one of a growing number of countries that has experienced the current globally popular tool of conflict resolution, the multi-party election. This method of endeavouring to put a final cap on a peace process has a mixed record in Africa. There have been some successes, but the installation of unsuitable over-powerful governments and/or the return to war have more often been the case. The article examines firstly the outcomes of the 2002 Sierra Leone elections, and then situates these consequences on a spectrum of African post-conflict elections outcomes. Finally, possibilities for avoiding or mitigating the negative effects of post conflict polls, particularly those emanating from the inevitable lack of security, are examined and posited.